2005
DOI: 10.2174/0929867054039071
|View full text |Cite
|
Sign up to set email alerts
|

Basement Membrane Peptides: Functional Considerations and Biomedical Applications in Autoimmunity

Abstract: Basement membranes are specialized extracellular matrices that surround certain cell types (muscle cells, adipose cells, etc) and are present under the basal surface of cells exhibiting polarity (epithelial, endothelial and mesothelial cells). They have a unique macromolecular composition, consisting mainly of type IV collagen isoforms, laminin isoforms, entactin/nidogen, and perlecan. These components self associate and interact with each other to form networks. Other macromolecules may be found in specialize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…The supramolecular structure of Col IV was extensively studied during the last two decades (Timpl and Brown, 1996;Gelse et al, 2003;White et al, 2004;Charonis et al, 2005;Brown et al, 2006;LeBleu et al, 2007;Khoshnoodi et al, 2008). Once secreted, the triple-helical heterotrimeric molecules of Col IV self-associate to form a 2D network which serves as molecular scaffold for other BM components, such as laminin, perlecans and proteoglycans (Timpl and Brown, 1996;Brown et al, 2006).…”
Section: Wwwecmjournalorg Nm Coelho Et Al Surface Assembly Of Typementioning
confidence: 99%
See 3 more Smart Citations
“…The supramolecular structure of Col IV was extensively studied during the last two decades (Timpl and Brown, 1996;Gelse et al, 2003;White et al, 2004;Charonis et al, 2005;Brown et al, 2006;LeBleu et al, 2007;Khoshnoodi et al, 2008). Once secreted, the triple-helical heterotrimeric molecules of Col IV self-associate to form a 2D network which serves as molecular scaffold for other BM components, such as laminin, perlecans and proteoglycans (Timpl and Brown, 1996;Brown et al, 2006).…”
Section: Wwwecmjournalorg Nm Coelho Et Al Surface Assembly Of Typementioning
confidence: 99%
“…Once secreted, the triple-helical heterotrimeric molecules of Col IV self-associate to form a 2D network which serves as molecular scaffold for other BM components, such as laminin, perlecans and proteoglycans (Timpl and Brown, 1996;Brown et al, 2006). Detailed in situ analysis of high resolution electron micrographs revealed that Col IV molecules self-assemble in the BM forming polygonal networks held together by overlapping and lateral interactions along the triple-helical domain and the N-and C-terminal end-domains ( Timpl and Brown, 1996;Charonis et al, 2005).…”
Section: Wwwecmjournalorg Nm Coelho Et Al Surface Assembly Of Typementioning
confidence: 99%
See 2 more Smart Citations
“…These include various collagens, elastin, fibronectin, laminin, fibulin, perlecan, entactin, and nidogen [7]. Among these, laminin is a glycoprotein produced mainly by epithelial cells and endothelial cells.…”
Section: Introductionmentioning
confidence: 99%